LEGAL IMPLICATION OF PLACING THE GOOGLE BALLOON IN NATIONAL AIR SPACE - Cholifah Damayanti; Anjar Supriadhie (Jurnal Dinamika Hukum, 2016)
The air space above the sovereignty of a state is closed to activities of other states except to getpermission from the subjacent state. Challenges and problems in the development and utilization ofnational air space region tend to increase and require problem solving prevention. One of them is theAmerican Google’s plan to cooperate with Indonesian government to put Google Balloon over the In-donesian national air space. The legal implications of this Google Balloon placement become the fo-cus of this study through system legal theory and legal effectiveness theory. Based on the resultsshow that First, from the legal substance aspect, status of Google Balloon cannot be categorized asan air or space vehicle; Second, viewed from the legal institutional aspects, the implementation ofthe project related to the competence of the relevant agencies which does not only involve the min-istry of communication and information but also involve the parliament; and Third, from the legalculture aspect, socialization towards the plan of the project needs to be expanded to prevent anyunfavorable circumstances.Keywords: Balloon Google, legal implications, the National Air Space